2014
DOI: 10.1155/2014/732163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zn/Fe Molar Ratio on Optical and Magnetic Properties of ZnO and ZnFe2O4Nanocrystal as Calcined Products of Layered Double Hydroxides

Abstract: The coprecipitation method has been used to synthesize layered double hydroxide (Zn-Fe-LDH) nanostructure at different Zn2+/Fe3+molar ratios. The structural properties of samples were studied using powder X-ray diffraction (PXRD). LDH samples were calcined at 600°C to produce mixed oxides (ZnO and ZnFe2O4). The crystallite size of mixed oxide was found in the nanometer scale (18.1 nm for ZnFe2O4and 43.3 nm for ZnO). The photocatalytic activity of the calcination products was investigated using ultraviolet-visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Zn-Fe-LDH has been formed by coprecipitaion of Zn(II) and Fe(III) nitrate solution using NaOH solution. Calcination of LDH not only changes hydroxide to oxide, but also removal of anion by thermal decomposition reaction Calcination of Zn-Fe-LDH forms ZnFe-LDO or ZnFe2O4 [16]. The ZnFe-LDO/AC composite from wood char showed good adsorption of paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Zn-Fe-LDH has been formed by coprecipitaion of Zn(II) and Fe(III) nitrate solution using NaOH solution. Calcination of LDH not only changes hydroxide to oxide, but also removal of anion by thermal decomposition reaction Calcination of Zn-Fe-LDH forms ZnFe-LDO or ZnFe2O4 [16]. The ZnFe-LDO/AC composite from wood char showed good adsorption of paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Although much less studied than Al-LDHs, MgRFe and ZnRFe LDHs have been reported for catalysis [78,79], agriculture [80], energy conversion/storage [81,82], as adsorbents for environmental remediation in its layered phases or as oxides after calcination [83][84][85][86][87][88][89][90][91][92][93], and more rarely for organic anions loading and delivery [94]. Ironbased LDHs (Fe 3+ -LDHs) are difficult to characterize due to their quite low crystallinity and the presence of crystalline and/or amorphous impurities.…”
Section: Iron-based Ldhs As Biomaterialsmentioning
confidence: 99%
“…Phase segregation also tends to occur when increasing the value of the M 2+ /Fe 3+ molar ratios, combined with the application of thermal treatment. Such conditions conduct to the appearance of XRD peaks not attributed to the corresponding LDH materials and frequently, for Zn-LDHs, peaks related to Zn(OH)2 and ZnO species [84,85,88,[98][99][100][101][102][103][104][105][106][107][108]. For instance, Morimoto et al [109] investigated the effect of different aging temperature values (25,50,75,100,125, and 150 °C ) on the formation of hematite in MgRFe-Cl (R = 2, 3, and 4) samples and observed that hematite formation is favored as higher the iron content and higher the temperature; this fact was explained by the decrease of LDH dehydroxylation temperature with the increase in the iron amount.…”
Section: Iron-based Ldhs As Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations